Videocolaboração no Hospital Militar de Área de São Paulo - Exército Brasileiro - Segobia, Mauricio M. M.; Novoa, Claudia Galindo; Silva, Cicero I. da; Melo, Paulo M. Porto de; Almeida, Jane de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This article analyzes the experience of the São Paulo Military Hospital (HMASP) in the area of digital health, telemedicine and telehealth. The goal is to present the state of the art of digital health at the HMASP, a history of its recent implementation and the challenges regarding the technological conditions existing in the field of videocolaboration for surgery and teleassistance. The article also analyzes some experiences in the area of telemedicine used at the HMASP by the Brazilian Army and also lists future challenges regarding the intensive use of videocolaborative processes in digital health.